The Effectiveness of Cognitive and Metacognitive Strategies in Learning English Vocabulary among Upper - Secondary Students in Three Southern Border Provinces of Thailand and Malaysia - Binmudnee, Pratya; Maduereh, Rokiyoh; Takaeh, Suinee (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
The vocabulary was the main factor in learning languages. The learners who knew the various vocabulary learning strategies and understood the meaning and the form of the vocabulary could better communicate with others. This research investigated the effectiveness of cognitive and metacognitive strategy use on teaching vocabulary skills among learners in three Southern Border Provinces of Thailand and Malaysia. The participants were 197 high school students studying in three Southern Border Provinces of Thailand and the border states of Malaysia, obtained through the purposive random sampling. Subjects were divided into 48 high students, 76 medium students, and 73 low students based on their percentage of the vocabulary achievement test. As the purpose of this study was to know the effectiveness of cognitive and metacognitive strategies in learning vocabulary of upper – secondary students who have the different English ability in three southern border provinces of Thailand and Malaysia, vocabulary learning strategies questionnaires, vocabulary test, and the interview were employed to find out what cognitive and metacognitive strategies had effects on students’ vocabulary performance. The data were analyzed by using mean and standard deviation. The research hypothesis was tested by two ways Anova F-test. The F- test value of the relation between vocabulary learning strategies and countries was 2.16 with the significance of .05. The findings revealed that the scores of the participants were positively and significantly correlated with cognitive and metacognitive strategy use.